Peraturan HAKI Sebagai Jaminan Fidusia oleh Pemerintahan Prabowo Gibran: Penelitian - Urbanisasi; Marsalina Susana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study examines the implementation of regulations governing Intellectual Property Rights (IPR) as fiduciary security under the Prabowo–Gibran administration by employing the principle of legal certainty as the primary analytical framework. The research is motivated by the gap between the normative framework (das Sollen), which legally recognizes IPR as a fiduciary object, and the empirical reality (das Sein) in which implementation remains constrained by the absence of technical guidelines, the lack of certified IPR appraisers, and the reluctance of financial institutions to accept intangible assets as collateral. Using a normative juridical method with statutory and conceptual approaches, this study analyzes the Fiduciary Law, sectoral IPR legislation, Government Regulation No. 24/2022, and academic literature. The findings indicate that the application of IPR as fiduciary collateral remains transitional and ineffective due to the unfulfilled elements of legal certainty, including clarity of norms, predictable procedures, and executable enforcement mechanisms. This research concludes that technical regulations, independent IPR appraisal bodies, administrative system integration, and institutional harmonization are essential to ensure that IPR can effectively serve as a viable financing instrument in Indonesia.